2010 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--16268
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Practices Of Engineering Capstone Design Teams

Abstract: Reflection is widely understood as a critical component of learning, especially learning from experience. Effective professionals learn from experiences and use this knowledge when encountering similar or more complex problems. The engineering capstone design course provides an excellent opportunity for students to gain experience in design, but experience alone does not guarantee learning of skills and knowledge, or the ability to transfer this knowledge to new situations. Researchers and theorists have long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The IDEALS teamwork curriculum has been implemented in part in capstone design courses at a number of institutions over recent years, as reported in other publications [10,30]. As discussed in this paper, it has been implemented more completely in the IRE problem-based learning program during academic year 2012-2013.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The IDEALS teamwork curriculum has been implemented in part in capstone design courses at a number of institutions over recent years, as reported in other publications [10,30]. As discussed in this paper, it has been implemented more completely in the IRE problem-based learning program during academic year 2012-2013.…”
Section: Resultsmentioning
confidence: 99%
“…From previous studies of IDEALS teamwork modules, the modules have been found to stimulate reflection and member behavior changes that enhance teamwork [10,30]. Twenty seven alumni from five institutions, a few months after graduation, responded to a questionnaire about the impacts of IDEALS teamwork modules on their preparation for professional practice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of this work engineering programs have begun to encourage students to engage in reflective practices that will facilitate the process of identifying transferable skills. 8,9,10 Capstone courses approximate professional practice thus serving as a natural transition between students' undergraduate experience and their work and lives after college. In an ideal world, students Page 22.1543.2…”
Section: Introductionmentioning
confidence: 99%